The impact of symptomatic chronic venous insufficiency (CVI) on health-related quality of life (HR Qol) in a multi-ethnics society in a developing nation - Abdul Rahman, Mohd Norhisham Azmi; Periasammy, Dineshwary; Nasreen, Hashima E; Elagili, Faisal; Othman, Ahmad Faidzal (Kulliyyah of Medicine, International Islamic University Malaysia (IIUM), 2024)
INTRODUCTION: Chronic venous insufficiency (CVI) is a common condition especially among those of advance age that is often neglected. As the disease severity progresses, it increases the healthcare cost and resources required, while diminishing the quality of life of the persons. Health-related Quality of Life (HRQoL) among CVI patients begins to decline once the symptom starts to appear, and reduces it further as the symptoms worsens. MATERIALS AND METHODS: This is a prospective, multi-centred, cross-sectional study on consenting symptomatic CVI patients who presented to the International Islamic University of Malaysia (IIUM) teaching hospital in Pahang, Malaysia. The diagnosis of CVI was confirmed on duplex imaging. Clinical grading was performed using Clinical Etiologic Anatomic Pathophysiologic (CEAP) classification. Patients completed generic validated Malay language Short Form 36 (SF36) HRQoL instrument. RESULTS: One hundred and ten patients (62% male) with a mean age of 57 years, Malays (60%), Chinese (25%) and Indian (15%) were recruited. The most frequent CVD symptoms reported were pain (42%). The clinical, aetiological, anatomical, and pathophysiological (CEAP) classification placed most patients in the C2 class (34%). Apart from partaking in social functions, all other elements of mental and physical health component of SF 36 showed a marked deterioration as the disease progressed. CONCLUSIONS: We found a significant decline in the HRQoL among symptomatic CVI patients presenting to IIUM hospital in a multi-ethnic developing country.